Effects of Rhodiola rosea and Withania somnifera powders on the functional and quality properties of chewing gum - Karatas, Mervenur; Ermis, Ertan; Saricaoglu, Beyza; Ozgolet, Muhammed (ELSEVIER, 2025)
Chewing gum is increasingly recognized as a promising carrier for functional ingredients, offering both convenience and consumer appeal. In this study, the effects of incorporating Rhodiola rosea (Golden Root, GR) and Withania somnifera (Indian Ginseng Root, IGR) powders into sugar-supplemented and sugar-free chewing gum formulations were investigated with respect to their functional and quality properties. Powder fractions of two particle size ranges (0-30 mu m and 30-60 mu m) were added at concentrations of 1 % and 3 % (w/w). Functional properties, including antioxidant activity and total phenolic content, as well as quality parameters such as texture, color, Fourier-transform infrared (FTIR) spectra, and thermal characteristics, were systematically analyzed. The results demonstrated that GR powder, particularly at 3 % concentration and 30-60 mu m size fraction, significantly enhanced total phenolic content and antioxidant activity compared to control samples, while IGR exhibited lower antioxidant potential. Texture analysis indicated that both GR and IGR powders increased gum hardness, with minimal effects on stickiness and chewiness, whereas color measurements confirmed that increasing powder concentration led to darker gum shades due to the inherent pigments of the root powders. FTIR and differential scanning calorimetry (DSC) analyses verified the structural integrity and thermal stability of the formulations, while principal component analysis (PCA) highlighted distinct clustering of GR- and IGR-fortified samples. Overall, this study demonstrates the feasibility of incorporating GR and IGR powders into chewing gum formulations as natural sources of bioactive compounds, although their influence on textural and sensory characteristics warrants further optimization.
Keywords: Chewing gum; Rhodiola rosea; Withania somnifera; Plant root powders; Adaptogens; CORN ZEIN; EXTRACT; SYSTEM; FORMULATION; TEXTURE; SUGAR; FTIR; MALTODEXTRIN; EVALUATE; SAFFRON; Food Science & Technology